Estimación del contenido de carbono de la cobertura forestal del bosque secundario kasama - González Paredes , Frank Elián (2024)
This research project was carried out in the Kasama protective forest, located in the Chigüilpe parish of the province of Santo Domingo de los Tsáchilas. The main objective was to estimate the carbon content present in the forest cover of the Kasama forest, in order to contribute to the knowledge of the carbon sequestration capacity of this ecosystem. The predominant vertical structure showed that the average height of most species was 13 m, however, in sampling unit 3 species exceeding 20 m were identified. Regarding the horizontal distribution of the sampled individuals, most species have wide crowns. The special distribution of these crowns reveals that there are areas with dense vegetation. The most abundant families were Urticaceae, with Moraceae also presenting high abundance according to the Importance Value Index (IVI) per family. Pourouma guianensis Aubl. It was the most abundant and dominant species in the plant community according to the IVI by species. The highest diversity according to the Shannon Index was recorded at 0.9147, the highest Simpson Index with an average of 2.709. The tree density was 243 ha-1, with a basal area of 26, 8 m2/ha and a volume of 326, 3 m3/ha. The family with the highest carbon storage was Moraceae, while Pourouma guianensis Aubl. as the most prominent species in terms of carbon storage by especies, with averages of 121,37 Mg and 112,84 Mg. An average of 1.1 t/ha of carbon stored in leaf litter and non living detritus was found, while an average of 2,95 t/ha was recorded in the understory biomass. The total organic carbon storage was 3, 86 t/ha in the range of 0 to 15 cm and 5, 84 t/ha-1 in the range of 15 to 30 cm. These results will be fundamental for future research related to the topic.